Occupational exposure to pesticides and its association with telomere length - A systematic review and meta-analysis - Passos, Jaqueline Dal Curtivo; Felisbino, Karoline; Laureano, Henrique Aparecido; Guiloski, Izonete Cristina (The Science of the total environment, 2022)
Telomere length is a common biomarker for the cumulative effect of environmental factors on aging-related diseases, therefore an association has been hypothesized between occupational exposure to pesticides and shorter telomere length. This study is a systematic review and meta-analysis aiming to examine the association between telomere length and occupational exposure to pesticides. We systematically searched in SciELO, PubMed, Scopus, Embase, Cochrane, Lilacs, Science Direct, and Web of Science databases for all observational studies containing measurements of telomere length on groups occupationally exposed to pesticides. Data were synthesized through qualitative synthesis and meta-analysis. We estimated the associations between exposed and non-exposed groups by using the natural log of the response ratio (lnRR). Heterogeneity was quantified using the Cochran Q test and I2 statistics. Six studies were included in the qualitative synthesis and meta-analysis, with a total of 480 participants exposed to pesticides. The time of exposure evaluated 391 participants that had a range of 5 to >30 years of occupational exposure. Most studies presented shorter telomere length in the occupationally exposed group. From the six studies included in the meta-analysis, three presented telomere length measurement as a single copy gene (T/S), and three presented telomere length measurement as base pairs (bp). The statistical analysis pooled estimates (log ratio of means) of the telomere length in both measurements (T/S and bp) showed a shortening of telomere length in the exposed group when compared with the non-exposed (control) group. Two of six studies reported longer telomere length in the group exposed to pesticides. Our findings suggest an association between occupational exposure to pesticides and shorter telomere length. However, we found a small number of studies to include in our meta-analysis, being required more high-quality studies to strengthen our findings and conclusions. [Display omitted] •Exposure to pesticides may be linked with genetic damage to the length of telomeres.•A meta-analytical review of the association between telomere length and pesticides.•Most workers exposed to pesticides had a shorter telomere length than a control group.•More studies with telomere length are needed to obtain a better pool of evidence.